The Many Lives of Mustard: Journey of a Familiar Condiment - Laurent, Christopher (Cuizine, 2013)
This paper takes the reader on a historical and global journey in search of mustard. Table mustard is part of a large family that also includes horseradish and wasabi. All three are used around the world as condiments and have a characteristic sting resulting from a complex organic protection mechanism. This burning sensation is at the heart of what unites all type of mustard users across time and space. Yet mustards are more than mere table condiments. They are the result of thousands of years of natural and selective breeding that have created plants with a unique biology. Eventually, societies learned to harness these active compounds for culinary use. Today, mustard is extensively produced in Canada and exported around the world as an essential component of contemporary gastronomy.